High expression of long non‐coding RNA AFAP1‐AS1 predicts chemoradioresistance and poor prognosis in patients with esophageal squamous cell carcinoma treated with definitive chemoradiotherapy - Zhou, Xi‐Lei (Mol Carcinog, 2016)
To evaluate the clinical significance of lncRNAs in the resistance to cisplatin‐based chemoradiotherapy in esophageal squamous cell carcinoma (ESCC). We focused on lncRNAs which were frequently reported in ESCC or were involved in chemoradiotherapy resistance. LncRNA expressions were examined in paired cisplatin‐resistant and parental ESCC cell lines. Dysregulated lncRNAs were further measured in 162 pretreatment biopsy specimens of ESCC who received definitive chemoradiotherapy (dCRT). Then the correlations between lncRNA expression and response to dCRT and prognosis were analyzed. Three lncRNAs (AFAP1‐AS1, UCA1, HOTAIR) were found to be deregulated in cisplatin‐resistant cells compared with their parent cells. AFAP1‐AS1 was significantly up‐regulated in tumor tissues compared with adjacent normal tissues (P = 0.006). Furthermore, overexpression of AFAP1‐AS1 was closely associated with lymph node metastasis (P < 0.001), distant metastasis (P = 0.016), advanced clinical stage (P = 0.002), and response to dCRT (P < 0.001). Kaplan–Meier survival analysis revealed that high expression of AFAP1‐AS1 was significantly associated with shorter progression free survival (PFS) (median, 15 months vs. 27 months, P < 0.001) and overall survival (OS) (median, 29 months vs. 42 months, P < 0.001). In the multivariate analysis, high expression of AFAP1‐AS1 was found to be an independent risk factor to predict poor PFS (HR, 1.626; P = 0.027) and OS (HR, 1.888; P = 0.004). Thus, high expression of AFAP1‐AS1 could serve as a potential biomarker to predict tumor response and survival. Determination of this lncRNA expression might be useful for selection ESCC patients for dCRT. © 2016 The Authors. Molecular Carcinogenesis published by Wiley Periodicals, Inc.